The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0101-81752003000200013
|View full text |Cite
|
Sign up to set email alerts
|

Lironeca desterroensis sp. nov. (Isopoda, Cymothoidae) from the gills of a marine fish, Cetengraulis edentulus Cuvier, of Santa Catarina Island, Brazil

Abstract: Lironeca desterroensis sp. nov. (Isopoda, Cymothoidae) is described on the basis of 105 females and three males taken from the gill chambers of the marine fish, Cetengraulis edentulus (Cuvier,1829), obtained near Santa Catarina Island, Brazil. The new species resembles Lironeca redmanni Leach, 1818, in size and general appearance but differs from that species in a number of important respects. In the new species, the pleotelson is larger, the pleonites are laterally produced, the uropods have elongate and slen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These results match other findings from the literature, where some studies of isopod parasites in other Brazilian coastal localities, showed that there were 75% prevalence of Livoneca redmanni in December and 44% for Rocinela signata in July for the host Scomberomorus brasiliensis (Lima et al, 2005). Other studies found 20% for Cymothoa catarinensis for the host Menticirrhus litoralis and 13% for Cymothoa excisa for the host Micropogonias furnieri (Thatcher et al, 2003a), and also the parasitism of Lironeca redmanni on Cetengraulis edentulus showed the prevalence of 17% (Thatcher et al, 2003b).…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 91%
“…These results match other findings from the literature, where some studies of isopod parasites in other Brazilian coastal localities, showed that there were 75% prevalence of Livoneca redmanni in December and 44% for Rocinela signata in July for the host Scomberomorus brasiliensis (Lima et al, 2005). Other studies found 20% for Cymothoa catarinensis for the host Menticirrhus litoralis and 13% for Cymothoa excisa for the host Micropogonias furnieri (Thatcher et al, 2003a), and also the parasitism of Lironeca redmanni on Cetengraulis edentulus showed the prevalence of 17% (Thatcher et al, 2003b).…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 91%
“…; mouth; marine; Rio de Janeiro (Thatcher 2000;2002). Lironeca desterroensis Thatcher, Souza-Conceição and Jost, 2003 Cetengraulis edentulus; gills; marine; Pará, Santa Catarina (Thatcher et al 2003c;Monfort et al 2009 (Sartor 1986). …”
Section: Cymothoa Excisa Perty 1833mentioning
confidence: 99%